Motivation and job satisfaction of quick-service restaurant employees in Klang Valley / Azdel Abdul Aziz … [et al.] - Abdul Aziz, Azdel; Mohd Khalid, Shariza; Ismail, Mohd Noor Ismawi; Ahmad, Noor Azmi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
A few changes in carrying out routine tasks during the post endemic created a new way of work environment. Practicing a new norm is a crucial practice in every industry or sector especially in Quick-Service Restaurants where the customers have close contact with the employees. This research aims to examine whether there is a positive impact of the Work Environment on employees’ Job Satisfaction. The data was collected by self-administered employees who worked with Quick-Service Restaurant in Klang Valley. Concerning this study, motivation factors are examined whether mediate the relationship between Work Environment and Job Satisfaction of the employees. There are five elements of Motivation which are Recognition, Work Itself, Growth, Achievement, and Advancement. Overall, this study provides an exciting opportunity to understand the responses and reactions to new norm practices among Quick-Service Restaurant employees